Gender Gaze Representation in American and South Korean Cinema: A Roland Barthes Semiotic Analysis - Theresia Tiffany; Krisopras Pison; Ni Putu Anindhitha Ayesha Sandra; Hedi Amelia Bella Chintya (Universitas Multimedia Nusantara, 2026)
This research is conducted to examine various representations of the gender gaze in cinema, specifically in American and South Korean cinemas, through the lens of Roland Barthes’ semiotic theory. The objective of this study is to analyze how both the male gaze and the female gaze are visualized and communicated through various cinematographic perspectives, such as visual signs and symbols, narrative structures, and even the cinematic techniques. Specifically, Barthes’ method of signification is used to interpret both explicit and implicit meanings constructed in the selected films from both countries. The results provide findings that American cinema tends to show more patriarchal visual ideology, which puts women as objects of the gaze, while South Korean cinema leans more toward women’s incremental transformation toward representations that are more balanced. Furthermore, this research concludes that the gender gaze in cinemas is mostly influenced by cultural and social aspects of the signified countries, as it represents the ideology that has been implemented in the society. In conclusion, this research provided complex insights into how cultural and social settings influence the cinematic gender gaze, therefore enhancing the understanding of gender representation and cross-cultural visual studies and offering valuable contributions to contemporary film production and analysis.